Dynamics of Hate Speech in Media Politics Social: Analysis of Fufufafa's Case Footprint on Facebook - Purnomo, Anisya Septiawati; Faradilah, Nur; Hafair, Arya Putra; Nisa, Pia Khoirotun (Journal of Social Science and Education Research, 2025)
Social media has become a platform that facilitates global interaction instantly. However, with this ease of access, the phenomenon of hate speech has emerged that affects political and social dynamics. The study analyzed the trail of "Fufufafa" cases on Facebook, focusing on the impact of hate speech in political discourse on social media. The study aims to understand how hate speech is spread and received by Facebook users, as well as its impact on social polarization. Using a content analysis approach, this study identifies communication patterns related to hate speech in the case, as well as how social media reinforces those narratives. The findings suggest that hate speech is often used as a political tool to mobilize support, incite hatred, and exacerbate social polarization. The study also highlights the role of social media algorithms in accelerating the spread of negative content and increasing exposure to certain groups. Thus, the results of this study are expected to provide insight for policymakers in dealing with the problem of hate speech in the digital space, especially in the political context on social media.